2002
DOI: 10.1038/416560a
|View full text |Cite|
|
Sign up to set email alerts
|

p63 and p73 are required for p53-dependent apoptosis in response to DNA damage

Abstract: The tumour-suppressor gene p53 is frequently mutated in human cancers and is important in the cellular response to DNA damage. Although the p53 family members p63 and p73 are structurally related to p53, they have not been directly linked to tumour suppression, although they have been implicated in apoptosis. Given the similarity between this family of genes and the ability of p63 and p73 to transactivate p53 target genes, we explore here their role in DNA damage-induced apoptosis. Mouse embryo fibroblasts def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
679
3
14

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 768 publications
(728 citation statements)
references
References 27 publications
32
679
3
14
Order By: Relevance
“…[22][23][24] Flores et al then observed that the p632/2; p732/2 double null mouse embryo fibroblasts (MEF) were as resistant to apoptosis as p532/2 MEF cells, pointing out that p63 and p73 are required for p53-induced apoptosis and delineating functional interplay between p53 family members. 25 More recent studies have shown that p73 could be implicated in the cellular response to drugs in cancer cells such as squamous cell carcinomas or osteosarcoma cell lines. [26][27] Today, there are no data regarding a hypothetical role of p73 and p63 in cellular response to ADR in p53-deficient breast cancers.…”
mentioning
confidence: 99%
“…[22][23][24] Flores et al then observed that the p632/2; p732/2 double null mouse embryo fibroblasts (MEF) were as resistant to apoptosis as p532/2 MEF cells, pointing out that p63 and p73 are required for p53-induced apoptosis and delineating functional interplay between p53 family members. 25 More recent studies have shown that p73 could be implicated in the cellular response to drugs in cancer cells such as squamous cell carcinomas or osteosarcoma cell lines. [26][27] Today, there are no data regarding a hypothetical role of p73 and p63 in cellular response to ADR in p53-deficient breast cancers.…”
mentioning
confidence: 99%
“…The significance of p63 and p73 binding to p53-responsive promoters, and the importance of each family member, is demonstrated by the fact that p53 cannot induce apoptosis in response to DNA damage, without the presence of p63 and p73. 74 In p63/p73 À/À double null mouse embryo fibroblasts (MEFs), the apoptotic genes Bax, Noxa and PERP were not induced in response to DNA damage, while p21 induction was normal. p53 was absent at the Bax, Noxa and PERP promoters when p63 and p73 were not there.…”
Section: Interaction On Promoters Of Target Genesmentioning
confidence: 99%
“…In some contexts, p63 and p73 are required for recruitment of p53 on pro-apoptotic target promoters. 72 It has also been demonstrated that the prolyl isomerase activity of Pin1 modifies p73 conformation, promoting its acetylation by p300/CBP in a cAbl-dependent fashion, and indeed under genotoxic stress, Pin1 is essential for p73's apoptotic activity. 68 This finding has important implications for cancer therapy, given p73's ability to determine chemosensitivity in some tumor cells lacking functional p53, 73 and also implicates Pin1 in coregulating p53 family members' activities.…”
Section: The Prolyl Isomerase Pin1mentioning
confidence: 99%